Women in Economics: A UK Perspective - Danula K. Gamage; Almudena Sevilla; Sarah Smith (Institute of Labor Economics (IZA), 2020)
The status of women in economics in the US has come increasingly under the spotlight. We exploit high quality administrative data to paint the first comprehensive picture of the status of women in UK academic economics departments in research-intensive universities. Our evidence indicates that, as in the US, women in economics are under-represented and are paid less than men. The issues facing women in economics in the UK are similar to other disciplines particularly STEM but have received less national policy attention to date. We conclude with a discussion of interventions that might improve the status of women in academia and we present new evidence that a UK academic diversity programme (Athena Swan) has narrowed the gender pay gap at a senior level.
Keywords: A14; 330; gender; affirmative action; academia; women in economics; gender wage gap